The Effectiveness of Social Interventions in Reducing Stigma of Covid-19 - Efendi Sianturi; Maida Pardosi; Elisabeth Surbakti; Rina Doriana Pasaribu (Jurnal Penelitian Pendidikan IPA, 2023)
Social stigma can encourage someone to hide their illness so they don't get society's discrimination. This study aims to analyze the effectiveness of social interventions to reduce stigma towards changes in the behavior of housewives in the prevention and control of Covid-19. The population in this study were all housewives in the research locus. Calculation of the minimum sample using a two-proportion hypothesis test for the intervention and control groups (n = 150). The selection of the sample used a simple random sampling technique. The intervention group was given a social intervention by a change agent for Covid-19. The controls were given government program interventions to prevent Covid-19. Respondent's behavior was measured before and after treatment using a questionnaire. Data were analyzed by paired t-test and independent t-test. The results of the study showed that social interventions through providing counseling by covid-19 change agents were more effective in reducing stigma through behavior change (p-value <0.05). The findings of this study can be a new understanding in the preparation of intervention programs for the prevention and control of infectious diseases related to stigma in general and Covid-19 in particular.Â